High-performance CuFe2O4 epitaxial thin films with enhanced ferromagnetic resonance properties. Issue 102 (21st October 2016) - Zhang, Ruyi; Liu, Ming; Lu, Lu; Mi, Shao-Bo; Jia, Chun-Lin; Wang, Hong
Abstract : CuFe2 O4 epitaxial films with superior FMR properties compared with bulk material have been successfully fabricated for the first time. Abstract : Highly epitaxial thin films of copper ferrite (CuFe2 O4 ) have been fabricated on MgAl2 O4 (001) substrates at a growth temperature of 400 °C for the first time, we believe, through a radio-frequency sputtering method. Structural analyses through high-resolution X-ray diffraction (HRXRD), Raman spectroscopy, and high-resolution transmission electron microscopy (HRTEM) all confirm the tetragonal spinel phase of CuFe2 O4 epitaxial film and high tetragonal distortion ( c / a = 1.08) of its unit cells. The 50 nm-thick T-CuFe2 O4 epitaxial film shows unique soft magnetism with small coercivity of 23 Oe and decreased magnetization. However, a superior ferromagnetic linewidth of only ∼93 Oe in the post-annealed T-CuFe2 O4 film compared with a linewidth of ∼1500 Oe in T-CuFe2 O4 single crystal bulk material is also observed, which indicates that epitaxial growth of oxide thin films combined with proper heat-treatment-induced cation engineering can impose novel functionalities.